The Father in the Communion of the Holy Trinity - Jagodziński, Marek (Teologia w Polsce, 2020)
Holy Trinity is the Communion of Persons. Relational understanding of Persons in the Holy Trinity is closely related to the concept of perichoresis. Most importantly, God is the Father. He is the Trinitarian source of Deity and exists in the Communion with the Son and the Holy Spirit. The mystery of love in God H.U. von Balthasar expresses with the help of the concept of kenosis, which did not take place only at the moment of incarnation or death of Jesus on the cross, but in God himself. In explaining of this image Balthasar does not use the full harmony of the meaning of communion, but dramatic metaphors of “killing”, “expropriation”, “separation” and even “absolute istinction” between the Father and Son. However, there is a question about the legitimacy of abandoning the metaphor of mutual community commonly used in Trinitology.